A Case Analysis of Olivia: Applying Gilligan’s Theory of Women’s Moral Development - Williams, Ginger (South Carolina College Personnel Association, 2013)
This article examines the case of “Olivia,” a young woman studying at a regional state university, to examine how one woman experienced the stages of Gilligan’s theory of women’s moral development. It begins with an introduction to Olivia’s background and her experience as a student in this community. Relevant student development theory, namely Carol Gilligan’s theory of women’s moral development, is reviewed. Through the lens of this particular theory, Olivia’s actions and beliefs are analyzed. The author attempts to locate Olivia at a specific level within the context of Gilligan’s framework. As Olivia was exposed to Gilligan’s theory and learned more about herself as an individual, the author suggested appropriate interventions to help guide her towards the next stage of development. The paper concludes with a reflection on how this case can help inform other practitioners.
Keywords: Student development theory; Gilligan’s theory of women’s moral development; Moral development; Women’s college development